Determination of pesticide residues level in phaseoulus vulgaris Sp. Plant Soil at Cameron Highland - Wong Yee Ching; N.A.M. Arifin; N.A. Atiqah (2013)
The application of pesticide is the best method to increase crops production yield. However it is also harmful to human health and the environment. The pesticides tested inthis study were Daconin, AntracolWP70 and Dithane M-45. They contain chlorothalonil, propined and mancozeb. A total of five soil samples were collected at 15 cm soil depth by systematic sampling